Blue Diatoms: Global Phenomenon of ˝Greening˝ in Shellfish and Record of Planktonic Haslea Species in the South Adriatic Sea - Maja Mejdandžić; Sunčica Bosak; Zrinka Ljubešić (Naše More (Dubrovnik), 2017)
Diatoms are unicellular, photoautotrophic eukaryotic microorganisms, often forming colonies and can be found in most aquatic and moist terrestrial habitats. All known diatoms today have specific golden-brown pigment fucoxanthin that masks chlorophylls in diatom plastid, but one genus represents an exception, having the additional specific pigment marennine due to whom the cells appear blue. Blue diatoms from genus Haslea cause a global phenomenon of ˝greening˝ in shellfish (mostly oysters) affecting them in both positive and negative ways. In this study, historical and recent review regarding blue diatoms and physiological and behavioural effect of marennine as well as challenges in shellfish farming from diatom perspective is addressed. This study is also a first record of blue Haslea diatom in the South Adriatic Sea during BIOTA (Bio-tracing Adriatic Water Masses) cruise in March 2016. Investigated blue diatom was cultured in laboratory and morphologically analysed with light microscopy. Diatom investigations are very important for better understanding of the ecology of specific marine area, but also for the economy, aquaculture and tourism. The emergence of green coloured flesh of shellfish in the Adriatic Sea has not been recorded yet, but this finding of the blue diatom from genus Haslea does not rule out this possibility in the future.